Islamic organisational culture for sustainable business futures: insights from Islamic scholars - Sharifah Rahama Amirul; Sharija Che Shaari; Sharifah Milda Amirul; Sorayah Nasip (Universiti Malaysia Sabah, 2024)
While establishing and pursuing a sustainable business future, organisational culture has taken central stage as the key enabler of organisational resilience, innovation, and ethical organisational governance. Conventional business frameworks and paradigms, which unduly marginalise the wealth of knowledge and wisdom of Islamic organisational culture, constitute a significant proportion of existing literature. Drawing inspiration from the deep well of Islamic wisdom, this paper offers insights and guidance on how organisations, guided by Islamic principles, can embrace and adapt their cultures to meet the demands of sustainable business practices and the evolving global landscape. Islamic teaching and values are deemed timeless; thus, drawing from qualitative focus group discussions with three engaged Islamic scholars as participants, the research seeks to identify valuable lessons on how the teachings of Islam can instill and sustain relevance and dynamism in organisational culture while adapting to modern demands. By highlighting the timelessness, universality, and adaptability of Islamic teachings, this study seeks to reaffirm their importance as a cornerstone for ethical and sustainable business practices. The insights gathered not only contribute to preserving Islamic culture within organisations but also provide a practical framework for businesses to navigate the complexities of the modern era while staying true to Islamic principles.